2017
DOI: 10.1097/j.pain.0000000000001096
|View full text |Cite
|
Sign up to set email alerts
|

Menthol reduces phototoxicity pain in a mouse model of photodynamic therapy

Abstract: Phototoxicity-induced pain is a major clinical problem triggered by light acting on photosensitising drugs or endogenous porphyrins, notably protoporphyrin IX (PpIX), an intermediary in heme biosynthesis. Protoporphyrin IX accumulates in individuals with erythropoietic protoporphyria and is elevated during photodynamic therapy subsequent to application of 5-aminolevulinic acid (ALA). Pain occurs during irradiation of PpIX and responds poorly to conventional analgesics. Our objective was to develop a model of P… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 42 publications
0
4
0
Order By: Relevance
“…These findings led to the proposal of a mechanism whereby TRPA1 and TRPV1 are activated by ROS, RNS, and/or RCS generated from Fe 3ϩ -catalyzed conversion of oxysterols that are produced by peroxidation of 7-DHC by singlet oxygen resulting from photochemical reactions involving endogenous chromophores (54). In contrast, TRPV1, but not TRPA1, appears to be implicated in the action potential firing of mouse DRG neurons triggered by protoporphyrin IX phototoxicity produced by 630-nm light (900).…”
Section: Activation By Lightmentioning
confidence: 99%
“…These findings led to the proposal of a mechanism whereby TRPA1 and TRPV1 are activated by ROS, RNS, and/or RCS generated from Fe 3ϩ -catalyzed conversion of oxysterols that are produced by peroxidation of 7-DHC by singlet oxygen resulting from photochemical reactions involving endogenous chromophores (54). In contrast, TRPV1, but not TRPA1, appears to be implicated in the action potential firing of mouse DRG neurons triggered by protoporphyrin IX phototoxicity produced by 630-nm light (900).…”
Section: Activation By Lightmentioning
confidence: 99%
“…The longer duration of analgesia may be explained by the existence of menthol and glycerin in compound lidocaine injection. Several literatures have identified the local anesthetic and analgesic effects of menthol, and the activity of menthol to enhance tissue permeability and facilitate local anesthetic delivery ( Gaudioso et al, 2012 ; Liu et al, 2013 ; Castro and Dent, 2017 ; Oz et al, 2017 ; Pergolizzi Jr. et al, 2018 ; Wright et al, 2018 ). The viscosity of glycerin allows local anesthetics to remain locally for a longer time.…”
Section: Discussionmentioning
confidence: 99%
“…Menthol is well recognized for its pharmacological properties of persistent analgesia and anesthesia via cumulative inactivation of voltage-gated sodium channels, blockade of neuronal calcium ion channels, inhibition of inflammation, and desensitization of nociceptive receptors ( Gaudioso et al, 2012 ; Liu et al, 2013 ; Oz et al, 2017 ; Pergolizzi Jr. et al, 2018 ; Wright et al, 2018 ). Furthermore, menthol has become the primary active ingredient and permeation enhancer for several topical analgesic formulations in clinics ( Castro and Dent, 2017 ; Pergolizzi Jr. et al, 2018 ).…”
Section: Introductionmentioning
confidence: 99%
“…A recent study also showed mechanistic differences between ALA and MAL, in that ALA‐PDT appeared to induce pain via singlet oxygen‐mediated lipid peroxidation, in turn triggering nociceptor activation via TRP cation channel subfamily V member 1 (TRPV1) receptors in dorsal root ganglia in vitro . Furthermore, the TRPV1 inhibitor menthol reduced action potentials evoked by ALA‐PDT in dorsal root ganglia and pain behaviour in a mouse model, although this was not the case with MAL‐PDT …”
Section: Painmentioning
confidence: 92%